Acceptability and feasibility of research grade wearables for monitoring heat stress in Kenyan farmers - Kwaro, Daniel; Mendt, Stefan; Okoth, Julius; Munga, Stephen; Gunga, Hanns-Christian; Heim, Zoë Hannah; Matzke, Ina; Bunker, Aditi; Barteit, Sandra; Maggioni, Martina Anna (npj digital medicine, 2025)
Abstract - Sub-Saharan Africa faces increasing heat events due to climate change, affecting health and productivity. Wearable technology, though promising for monitoring these impacts, is underexplored in this region. This pilot study evaluated the acceptability and feasibility of research-grade wearables for monitoring heat stress among Kenyan subsistence farmers. In Siaya, 48 farmers (50% women) were monitored for 14 days using sensors to measure heart rate, core temperature, sleep, activity, and geo-location, alongside environmental data loggers for wet bulb globe temperature. Participants mostly rated their experience on a 5-point Likert scale and provided additional non-Likert feedback, with over 95% reporting high device likability and minimal disruption. Data availability was 88% for actigraphy and 100% for core temperature, with a median completeness of 100% for most devices. Women experienced greater heat strain than men. These findings demonstrate that research-grade wearables are acceptable and feasible for real-time heat stress monitoring in rural Africa.
Gesehen am 09.10.2025